Hydrogen-permeation-resistant composite coating for hydrogen conveying pipeline and preparation method of hydrogen-permeation-resistant composite coating

By applying a hydrogen permeability composite coating composed of silicon carbide powder and organic resin on the hydrogen transport pipeline, the problem of hydrogen permeability and corrosion in hydrogen energy transportation is solved, and higher corrosion resistance and hydrogen resistance are achieved Performance, extends the service life of the pipe and improves safety.

CN119463553APending Publication Date: 2025-02-18HARBIN INST OF TECH

Patent Information

Application Number
CN202411611307.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Hydrogen transmission pipeline steel is prone to hydrogen seepage and corrosion during hydrogen energy transportation, resulting in low safety and difficult to meet the large-scale and long-distance hydrogen transmission needs.

Method used

A hydrogen permeability composite coating is adopted, which consists of silicon carbide powder, silicon carbide fibers, modified silicon carbide powder and organic resin. Through a simple preparation process and a low-cost method, a coating of 200-500μm thick is formed. layer, enhances the corrosion and hydrogen resistance of the pipeline.

Benefits of technology

It significantly improves the anti-hydrogen permeability and corrosion resistance of hydrogen transmission pipelines, extends the service life of the pipeline, reduces the energy waste and pollution caused by hydrogen penetration, and improves the operation safety of hydrogen transmission pipelines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463553A_ABST
    Figure CN119463553A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-hydrogen-permeation composite coating for a hydrogen conveying pipeline and a preparation method of the anti-hydrogen-permeation composite coating, and belongs to the field of physically modified metal corrosion prevention. The method comprises the following steps: step 1, firstly weighing quantitative silicon carbide powder, silicon carbide fiber and modified silicon carbide powder, adding a dispersing agent for dispersing, and uniformly stirring under the action of magnetic stirring; step 2, adding quantitative organic resin and a curing agent thereof in the step 1, further stirring uniformly, defoaming under a vacuum condition, and removing bubbles and a dispersing agent therein; and thirdly, the steel plate is pretreated, then the steel plate is evenly coated with the coating, and the stable coating can be obtained through normal-temperature curing and heating curing. The preparation method of the coating is easy to operate, low in cost and high in hydrogen permeability resistance, the service life of the hydrogen conveying pipeline can be effectively prolonged, and the hydrogen conveying efficiency and the pipeline safety are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of physically modified metal corrosion protection, and in particular relates to a hydrogen permeation resistant composite coating for a hydrogen transmission pipeline and a preparation method thereof. Background Art

[0002] At present, the global energy demand is rising. Due to the unsustainability of fossil energy, the development of new energy has become urgent. The use of sustainable new energy such as wind energy, solar energy, tidal energy, and hydrogen energy can alleviate the development problems caused by the shortage of fossil energy, reduce the environmental burden, and protect the sustainable development of the ecology. However, there are great limitations in the actual application of new energy. As one of the clean energy sources, hydrogen energy has high energy conversion efficiency and strong environmental protection. Various places actively encourage the use of clean energy, but there are certain problems in the transportation of hydrogen energy. It is difficult to achieve high-pressure long-line transportation, and it is impossible to achieve high-efficiency transportation and use of hydrogen energy. Hydrogen energy transportation is the key to the development of the hydrogen energy industry. At present, the safety of hydrogen pipelines cannot be guaranteed. Among them, the failure of pipeline steel caused by hydrogen embrittlement is the main problem, which has attracted widespread attention. Hydrogen embrittlement refers to the fact that after excessive hydrogen atoms enter the metal matrix, under the action of stress, the toughness or bearing capacity of the metal is reduced, resulting in fracture or sudden brittle failure.

[0003] Pipeline steel is often used in hydrogen transmission pipelines. To prevent hydrogen embrittlement, a coating that delays hydrogen permeation is often applied on its surface. The coating design is mainly based on two aspects. On the one hand, the coating has good density and good physical barrier properties, which can effectively prevent hydrogen from entering or extend the hydrogen diffusion path; on the other hand, hydrogen traps are created to capture and fix hydrogen atoms, thereby reducing the hydrogen diffusion concentration in the material.

[0004] At present, common anti-hydrogen permeation coatings include silicide coatings, metal oxide coatings, composite polymer coatings, etc. Different coatings have different preparation processes, such as chemical / physical vapor deposition, plasma spraying, etc. The preparation process required for large-scale, long-distance hydrogen pipeline steel is simple and low-cost, but some of the above methods are not suitable for large-scale, long-distance batch production. Moreover, the basic mechanical properties of the coating must meet the requirements of actual production applications. The anti-hydrogen permeation coating must not only meet the requirements of hydrogen permeation resistance, but also meet the requirements of long-term corrosion protection. It is necessary to design the composition and structure of the coating from the above two aspects to improve the safety of hydrogen pipeline steel and meet the long-term needs of industrial development. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of hydrogen permeation and easy corrosion of hydrogen pipeline steel, and to provide a hydrogen permeation resistant composite coating for hydrogen pipeline and a preparation method thereof. The coating preparation process is simple and the cost is low.

[0006] The present invention is achieved through the following technical solutions:

[0007] A hydrogen permeation-resistant composite coating for a hydrogen transmission pipeline, the coating comprising component A and component B; the component A is one or more of silicon carbide powder, silicon carbide fiber, and modified silicon carbide powder; the component B is an organic resin.

[0008] Furthermore, the organic resin is one or more commercial brands of organic resins; the organic resin curing agent used is one or more of an amine curing agent, an acid anhydride curing agent, and a synthetic resin curing agent.

[0009] Furthermore, the particle sizes of the silicon carbide powder, silicon carbide fiber and modified silicon carbide powder are all 60-140 nm; and the thickness of the coating is 200-500 μm.

[0010] Furthermore, the content of component A is 3wt.%-20wt.%, and the coating quality is good.

[0011] Furthermore, the hydrogen transmission pipeline is one or more of pipeline steel, copper pipe or plate.

[0012] A method for preparing the above-mentioned hydrogen permeation-resistant composite coating for hydrogen transmission pipelines, the method comprising:

[0013] Step 1: Mix component A and the dispersant evenly, and stir for 10-30 minutes to obtain a mixture A;

[0014] Step 2: Add component B to mixture A, increase the stirring speed, and stir for 20-50 minutes to obtain mixture B;

[0015] Step 3: Add curing agent to mixture B and continue stirring for 20-50 minutes to obtain mixture C;

[0016] Step 4: Place mixture C in a vacuum defoaming barrel and perform vacuum defoaming for 5-15 minutes to obtain mixture D;

[0017] Step 5: Brush the mixture D onto the hydrogen pipeline substrate (steel plate), cure it at room temperature for 24 hours, and dry it at 50°C in a vacuum for 4 hours to obtain a stable coating.

[0018] Furthermore, the weight ratio of the component A to the dispersant is 1:5-10; and the mass ratio of the organic resin to the curing agent is 1:1.

[0019] Furthermore, before the mixture D is applied to the surface of the hydrogen pipeline substrate, a pretreatment is performed (grinding with sandpaper, cleaning with anhydrous ethanol, and drying); the purpose of the pretreatment is to keep the surface of the steel plate clean so as not to hinder the coating effect. The pretreatment includes degreasing and descaling, removing the oxide layer, and removing surface impurities.

[0020] Furthermore, the method for removing oil and scale is to wipe the steel plate with a wet cloth dipped in decontamination powder, and then rinse with ultrapure water after wiping; the method for removing the oxide layer is to mechanically polish the surface of the steel plate after degreasing and descaling using sandpaper of different mesh sizes from small to large; the method for removing surface impurities is to place the steel plate after the oxide layer is removed in ultrapure water and anhydrous ethanol, and ultrasonicate for 5 to 10 minutes respectively, and perform cold air drying after each ultrasonication.

[0021] Furthermore, the dispersant includes anhydrous ethanol and n-butanol, and the ratio of the two is 1:1.5-0.

[0022] The beneficial effects of the present invention relative to the prior art are as follows: the anti-hydrogen penetration composite coating of the present invention is an inorganic and organic composite coating, wherein silicon carbide powder, silicon carbide fiber, and silicon carbide composite ceramic powder are all granular materials, have strong anti-hydrogen penetration ability, and have the potential of a new type of hydrogen barrier layer. Silicon carbide powder, silicon carbide fiber, and silicon carbide composite ceramic powder are all easy to combine with hydrogen and are potential hydrogen storage materials. After silicon carbide powder, silicon carbide fiber, or silicon carbide composite ceramic powder is filled into an organic resin, the free volume of the organic resin is reduced, the difficulty of hydrogen diffusion is increased, and at the same time, it can be used as a site to adsorb and fix hydrogen, increase hydrogen traps, reduce the hydrogen diffusion coefficient, and significantly improve the anti-corrosion performance of the composite coating, which is also necessary under actual working conditions in the pipeline. The present invention combines the advantages of inorganic fillers and organic coatings. In the development of hydrogen energy production, it can extend the service life of hydrogen pipelines to a limited extent, effectively reduce the energy waste and pollution caused by hydrogen penetration, and improve the safety of hydrogen pipeline operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is an electrochemical hydrogen permeation curve diagram of Example 1;

[0024] Figure 2 is an electrochemical hydrogen permeation curve diagram of Example 2;

[0025] Figure 3 is an electrochemical hydrogen permeation curve diagram of Example 3;

[0026] Figure 4 is an electrochemical hydrogen permeation curve diagram of Comparative Example 1;

[0027] Figure 5 is a SEM image of Example 1 before the electrochemical hydrogen permeation performance test;

[0028] Figure 6 is a SEM image of Example 1 after the electrochemical hydrogen permeation performance test;

[0029] Figure 7 is a surface morphology of the filler of Example 1;

[0030] Figure 8This is the surface morphology of the filler in Example 2. DETAILED DESCRIPTION

[0031] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0032] A method for preparing a hydrogen permeation resistant coating for a hydrogen transmission pipeline, comprising:

[0033] (1) Preparation of coating: Weigh a certain amount of silicon carbide powder, silicon carbide fiber or silicon carbide composite ceramic powder, mix it with a dispersant, and stir it with a magnetic stirrer for 15 minutes to obtain component A; add an organic resin to component A, increase the stirring speed and continue stirring for 20 minutes to obtain component B; add a curing agent to component B, and continue stirring for 20 minutes to obtain component C; put component C into a vacuum defoaming barrel and vacuum defoam to obtain silicon carbide powder, silicon carbide fiber, silicon carbide composite ceramic powder coating;

[0034] (2) Pre-treating the steel plate by first grinding it with sandpaper, cleaning it with anhydrous ethanol, and after drying, brushing the silicon carbide powder, silicon carbide fiber, and silicon carbide composite ceramic powder coating of step (1) on the surface of the substrate, curing it at room temperature for 24 hours, and drying it at 50° C. in a vacuum chamber for 4 hours to obtain a stable coating.

[0035] Embodiment 1:

[0036] Select Q235 steel as the base material with a size of 50mm*50mm*1mm. The specific steps are as follows:

[0037] (1) Degreasing and descaling treatment on both sides of the steel plate:

[0038] The method for removing oil and scale is to wipe the steel plate with a wet cloth dipped in detergent powder, and then rinse it ultrasonically with ultrapure water for 5 minutes.

[0039] (2) Remove the oxidation layer from both sides of the steel plate:

[0040] The method for removing the oxide layer is: use 1000#, 1500#, and 2000# sandpaper to mechanically polish the degreased and descaled steel plate surface for 5 minutes respectively.

[0041] (3) Remove impurities from both sides of the steel plate:

[0042] The method for removing surface impurities is as follows: the steel plate after the oxide layer is removed is placed in ultrapure water and anhydrous ethanol for ultrasonic treatment for 10 minutes respectively, and cold air drying is performed after each ultrasonic treatment.

[0043] (4) One side of the steel plate is nickel-plated;

[0044] (5) Coating treatment on the other side of the steel plate:

[0045] First, weigh 0.3860g of 60nm silicon carbide powder and add it to the dispersant, the ratio of silicon carbide powder to dispersant is 1:3, stir evenly, and stir for about 10 minutes; then weigh 2.0g of organic resin (E51 type) and add it to the dispersed system, then stir evenly, and stir for about 20 minutes; weigh 2.0g of curing agent and add it to the mixed system, continue to stir evenly, and stir for about 20 minutes; put the evenly stirred system into a vacuum defoaming barrel, vacuum defoam, and the vacuuming time is 6 minutes; apply the bubble-free paint on the steel plate with a brush, dry at room temperature for 24 hours, and then vacuum dry at 50°C for 4 hours to obtain a stable coating.

[0046] The hydrogen barrier coating prepared in this embodiment has good hydrogen barrier properties. Figure 1 In the electrochemical hydrogen permeation test at room temperature, its hydrogen resistance is about 96 times that of Q235 steel. Figure 5 and Figure 6 This is a comparison chart before and after the electrochemical hydrogen permeation test. The coating is basically not damaged and the quality is stable.

[0047] Embodiment 2:

[0048] Select Q235 steel as the base material with a size of 50mm*50mm*1mm. The specific steps are as follows:

[0049] (1) Degreasing and descaling treatment on both sides of the steel plate:

[0050] The method for removing oil and scale is to wipe the steel plate with a wet cloth dipped in detergent powder, and then rinse it ultrasonically with ultrapure water for 5 minutes.

[0051] (2) Remove the oxidation layer from both sides of the steel plate:

[0052] The method for removing the oxide layer is: use 1000#, 1500#, and 2000# sandpaper to mechanically polish the degreased and descaled steel plate surface for 5 minutes respectively.

[0053] (3) Remove impurities from both sides of the steel plate:

[0054] The method for removing surface impurities is as follows: the steel plate after the oxide layer is removed is placed in ultrapure water and anhydrous ethanol for ultrasonic treatment for 10 minutes respectively, and cold air drying is performed after each ultrasonic treatment.

[0055] (4) One side of the steel plate is nickel-plated;

[0056] (5) Coating treatment on the other side of the steel plate:

[0057] First, weigh 0.3860g of 140nm silicon carbide powder and add it to the dispersant, stir evenly, and stir for about 10 minutes; then weigh 2.0g of organic resin (E51 type) and add it to the dispersed system, then stir evenly, and stir for about 20 minutes; weigh 2.0g of curing agent and add it to the mixed system, continue to stir evenly, and stir for about 20 minutes; put the evenly stirred system into a vacuum defoaming barrel, vacuum defoam, and the vacuuming time is 6 minutes; apply the bubble-free paint on the steel plate with a brush, dry at room temperature for 24 hours, and then vacuum dry at 50°C for 4 hours to obtain a stable coating.

[0058] The hydrogen barrier coating prepared in this embodiment has good hydrogen barrier properties. Figure 2 In the electrochemical hydrogen permeation test at room temperature, its hydrogen resistance is about 25 times that of Q235 steel.

[0059] Embodiment 3:

[0060] Select Q235 steel as the base material with a size of 50mm*50mm*1mm. The specific steps are as follows:

[0061] (1) Degreasing and descaling treatment on both sides of the steel plate:

[0062] The method for removing oil and scale is to wipe the steel plate with a wet cloth dipped in detergent powder, and then rinse it ultrasonically with ultrapure water for 5 minutes.

[0063] (2) Remove the oxidation layer from both sides of the steel plate:

[0064] The method for removing the oxide layer is: use 1000#, 1500#, and 2000# sandpaper to mechanically polish the degreased and descaled steel plate surface for 5 minutes respectively.

[0065] (3) Remove impurities from both sides of the steel plate:

[0066] The method for removing surface impurities is as follows: the steel plate after the oxide layer is removed is placed in ultrapure water and anhydrous ethanol for ultrasonic treatment for 10 minutes respectively, and cold air drying is performed after each ultrasonic treatment.

[0067] (4) One side of the steel plate is nickel-plated;

[0068] (5) Coating treatment on the other side of the steel plate:

[0069] Synthesize modified silicon carbide powder filler: first weigh 1.3065g cerium nitrate and 0.8g silicon carbide powder into a beaker, add 70ml deionized water and stir for 15 minutes; then add 1.5ml ammonia water dropwise and continue stirring for 10 minutes; after adding 100μL hydrogen peroxide, increase the magnetic stirring; then add 100μL FAS (triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane) and continue stirring for 10 minutes; then transfer to a reactor at high temperature for 2 hours, then wash and filter with anhydrous ethanol and ultrapure water, and put into an oven at 60°C to dry for 6 hours.

[0070] Coating preparation: first weigh 0.3860g of modified silicon carbide powder and add it to the dispersant, stir evenly, and stir for about 10 minutes; then weigh 2.0g of organic resin (type E51) and add it to the dispersed system, then stir evenly, and stir for about 20 minutes; weigh 2.0g of curing agent and add it to the mixed system, continue to stir evenly, and stir for about 20 minutes; put the evenly stirred system into a vacuum defoaming barrel, vacuum defoam, and the vacuuming time is 6 minutes; apply the bubble-free coating on the steel plate with a brush, dry at room temperature for 24 hours, and then vacuum dry at 50°C for 4 hours to obtain a stable coating.

[0071] The hydrogen barrier coating prepared in this embodiment has good hydrogen barrier properties. Figure 3 In the electrochemical hydrogen permeation test at room temperature, its hydrogen resistance is about 5 times that of Q235 steel.

[0072] Comparative Example 1:

[0073] Select Q235 steel as the base material with a size of 50mm*50mm*1mm. The specific steps are as follows:

[0074] (1) Degreasing and descaling treatment on both sides of the steel plate:

[0075] The method for removing oil and scale is to wipe the steel plate with a wet cloth dipped in detergent powder, and then rinse it ultrasonically with ultrapure water for 5 minutes.

[0076] (2) Remove the oxidation layer from both sides of the steel plate:

[0077] The method for removing the oxide layer is: use 1000#, 1500#, and 2000# sandpaper to mechanically polish the degreased and descaled steel plate surface for 5 minutes respectively.

[0078] (3) Remove impurities from both sides of the steel plate:

[0079] The method for removing surface impurities is as follows: the steel plate after the oxide layer is removed is placed in ultrapure water and anhydrous ethanol for ultrasonic treatment for 10 minutes respectively, and cold air drying is performed after each ultrasonic treatment.

[0080] The hydrogen permeation evaluation of Examples 1-2 and Comparative Example 1 was tested by an electrochemical hydrogen permeation method. First, nickel plating was performed on one side. The nickel plating was to improve the detection sensitivity of hydrogen and reduce the residual current. After the electroplating was completed, ultrapure water and anhydrous ethanol were used to rinse, and then cold air was used to dry. A double-sided electrolytic cell was used, and Pt electrodes were used as the counter electrodes of the anode cell and the cathode cell. The effective area of ​​the Pt electrode sheet was 1-10 cm 2 , using saturated calomel electrode as reference electrode, the electrolyte added to the anode cell is 0.2mol / L NaOH aqueous solution, and the poisoning agent added to the cathode cell is 1-3g / L thiourea; the anode cell voltage is set to 0.15-0.3V relative to the reference electrode, and the cathode cell is charged with hydrogen at a constant current after the background current stabilizes, and the hydrogen charging current is 10-50mA / cm 2 .

[0081] Table 1 is the test results of Examples 1-2 and Comparative Example 1

[0082] Test duration / h Hydrogen permeation current / μA Example 1 19.88 0.0925 Example 2 20.52 0.4387 Example 3 19.59 1.8934 Comparative Example 1 16.68 8.9490

[0083] The above is only a preferred embodiment of the present invention and does not limit the invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, other equivalent improvements can be made, all of which can achieve the purpose of the present invention and should be regarded as the protection scope of the present invention.

Claims

1. A hydrogen permeation resistant composite coating for a hydrogen transport pipeline, characterized in that: The coating comprises component A and component B; component A is one or more of silicon carbide powder, silicon carbide fiber, and modified silicon carbide powder; and component B is an organic resin.

2. The hydrogen permeation resistant composite coating for hydrogen transport pipeline according to claim 1, characterized in that: The organic resin is one or more commercially available organic resins; the organic resin curing agent used is one or more amine curing agents, acid anhydride curing agents, and synthetic resin curing agents.

3. The hydrogen permeation resistant composite coating for hydrogen transport pipeline according to claim 1, characterized in that: The particle sizes of the silicon carbide powder, silicon carbide fiber and modified silicon carbide powder are all 60-140 nm; the thickness of the coating is 200-500 μm.

4. The hydrogen permeation resistant composite coating for hydrogen transport pipeline according to claim 1, characterized in that: The content of component A is 3wt.%-20wt.%.

5. The hydrogen permeation resistant composite coating for hydrogen transport pipeline according to claim 1, characterized in that: The hydrogen transmission pipeline is one or more of pipeline steel, copper pipe or plate.

6. A method for preparing a hydrogen permeation resistant composite coating for a hydrogen transport pipeline according to any one of claims 1 to 5, characterized in that: The method is: Step 1: Mix component A and the dispersant evenly, and stir for 10-30 minutes to obtain a mixture A; Step 2: Add component B to mixture A, increase the stirring speed, and stir for 20-50 minutes to obtain mixture B; Step 3: Add curing agent to mixture B and continue stirring for 20-50 minutes to obtain mixture C; Step 4: Place mixture C in a vacuum defoaming barrel and perform vacuum defoaming for 5-15 minutes to obtain mixture D; Step 5: Brush the mixture D onto the hydrogen pipeline substrate (steel plate), cure it at room temperature for 24 hours, and dry it at 50°C in a vacuum for 4 hours to obtain a stable coating.

7. The preparation method according to claim 6, characterized in that: The weight ratio of component A to the dispersant is 1:5-10; the mass ratio of the organic resin to the curing agent is 1:

1.

8. The preparation method according to claim 6, characterized in that: Before the mixture D is applied to the surface of the hydrogen pipeline substrate, a pretreatment is performed, which includes removing oil and scale, removing oxide layers and removing surface impurities.

9. The preparation method according to claim 8, characterized in that: The method for removing oil and scale is to wipe the steel plate with a wet cloth dipped in decontamination powder, and then rinse with ultrapure water; the method for removing the oxide layer is to mechanically polish the surface of the steel plate after degreasing and descaling using sandpaper of different mesh sizes from small to large; the method for removing surface impurities is to place the steel plate after the oxide layer is removed in ultrapure water and anhydrous ethanol, and ultrasonicate for 5 to 10 minutes respectively, and perform cold air drying after each ultrasonication.

10. The preparation method according to claim 6, characterized in that: The dispersant includes anhydrous ethanol and n-butanol, and the ratio of the two is 1:1.5-0.

Citation Information

Patent Citations

  • Anti-hydrogen corrosion-resistant coating and preparation method

    CN107916045A

  • Coating material which prevent hydrogen embrittlement

    JP1990060967A

Cited By

  • Hydrogen-resistant coating paint and hydrogen conveying pipeline

    CN120699508A